Examining the Relationship between Cultural Competence and Internationalisation: A Study on the British University in Egypt - Morsi, Lamis; Kortam, Wael (Archives of Business Research, 2022)
With the on-going integration of the global economy, individuals from distinct cultural backgrounds need to be catered to by businesses as well as from international managers; therefore, cultural competence is highly expected from individuals going abroad. The contemporary trend headed for internationalisation has placed major emphasis on individuals being culturally competent. Therefore, this research aims to examine the relationship between cultural competence and internationalisation. Cultural competence as a construct in this research is looked at through five dimensions adapted from The International Profiler by Spencer Oatey & Franklin (2009) which are: cultural knowledge, flexibility, influencing, synergy, and listening orientation. These dimensions are examined in relation to actual internationalisation as well as an individual’s desirability to internationalise. This relationship is examined on academics throughout various faculties in The British University in Egypt with a main focus on Teaching Assistants. Data was collected through an online questionnaire as well as an interview was conducted. The results proved that there is a relationship between the variables. Synergy as a dimension of cultural competence has proved to have a significant and positive relationship with internationalisation. Moreover, cultural knowledge and influencing have also proved to have a significant and positive relationship with the desirability to internationalise.